RyR2-Mediated Ca2+ Release and Mitochondrial ROS Generation Partake in the Synaptic Dysfunction Caused by Amyloid β Peptide Oligomers - SanMartín, Carol D.; Veloso, Pablo; Adasme, Tatiana; Lobos, Pedro; Bruna, Barbara; Galaz, Jose; García, Alejandra; Hartel, Steffen; Hidalgo, Cecilia; Paula-Lima, Andrea C. (Frontiers in Molecular Neuroscience, 2017)
Amyloid β peptide oligomers (AβOs), toxic aggregates with pivotal roles in Alzheimer´s disease, trigger persistent and low magnitude Ca2+ signals in neurons. We reported previously that these Ca2+ signals, which arise from Ca2+ entry and subsequent amplification by Ca2+ release through ryanodine receptor (RyR) channels, promote mitochondrial network fragmentation and reduce RyR2 expression. Here, we examined if AβOs, by inducing redox sensitive RyR-mediated Ca2+ release, stimulate mitochondrial Ca2+-uptake, ROS generation and mitochondrial fragmentation, and also investigated the effects of the antioxidant N-acetyl cysteine (NAC) and the mitochondrial antioxidant EUK-134 on AβOs-induced mitochondrial dysfunction. In addition, we studied the contribution of the RyR2 isoform to AβOs-induced Ca2+ release, mitochondrial Ca2+ uptake and fragmentation. We show here that inhibition of NADPH oxidase type-2 prevented the emergence of RyR-mediated cytoplasmic Ca2+ signals induced by AβOs in primary hippocampal neurons. Treatment with AβOs promoted mitochondrial Ca2+ uptake and increased mitochondrial superoxide and hydrogen peroxide levels; ryanodine, at concentrations that suppress RyR activity, prevented these responses. The antioxidants NAC and EUK134 impeded the mitochondrial ROS increase induced by AβOs. Additionally, EUK- 134 prevented the mitochondrial fragmentation induced by AβOs, as previously reported for NAC and ryanodine. These findings show that both antioxidants, NAC and EUK-134, prevented the Ca2+-mediated noxious effects of AβOs on mitochondrial function. Our results also indicate that Ca2+ release mediated by the RyR2 isoform causes the deleterious effects of AβOs on mitochondrial function. Knockdown of RyR2 with antisense oligonucleotides reduced by about 50% RyR2 mRNA and protein levels in primary hippocampal neurons, decreased by 40% Ca2+ release induced by the RyR agonist 4-chloro-m-cresol, and significantly reduced the cytoplasmic and mitochondrial Ca2+ signals and the mitochondrial fragmentation induced by AβOs. Based on our results, we propose that AβOs-induced Ca2+ entry and ROS generation jointly stimulate RyR2 activity, causing mitochondrial Ca2+ overload and fragmentation in a feed forward injurious cycle. The present novel findings highlight the specific participation of RyR2-mediated Ca2+ release on AβOs-induced mitochondrial malfunction.